Isolated females and limited males: evolution of insect resistance in structured landscapes. Issue 1 (4th December 2012) - Spencer, Joseph; Onstad, David; Krupke, Christian; Hughson, Sarah; Pan, Zaiqi; Stanley, Bruce; Flexner, Lindsey
Abstract To delay evolution of insect resistance to insecticidal Bacillus thuringiensisBerliner (Bt) transgenic crops, USA and Canadian maize growers commonly set aside a portion of each field as a refuge, where susceptible pests can develop without exposure to the toxin(s) expressed in the insecticidal crop. Abundant mate‐seeking refuge adults are expected to move into insecticidal crop areas and mate with rare, resistant insects. Production of heterozygous offspring, rather than homozygous offspring reduces the rate of resistance evolution. Expectations about the refuge strategy are predicated on assumptions about when and where pest insects move and mate. Accumulating evidence indicates that the behavior of western corn rootworm beetles, Diabrotica virgifera virgiferaLeConte (Coleoptera: Chrysomelidae) (WCR), in refuge and corn rootworm (CRW)‐active Bt‐transgenic maize does not always conform to assumptions about random mating and individual movement. Contrary to expectations, up to 23.6% of unmated refuge females left refuge and were non‐teneral by the time they mated in CRW‐active maize. Consequences of protandry, limited male mating capacity, pre‐mating male and female movement patterns, skewed sex ratios, and delayed adult emergence from CRW‐active maize all may contribute to unexpected or undesirable patterns of WCR reproductive behavior. Modeling suggests that temporal and spatial components of WCR mating that limit interactions in block refuges can be reduced by deploying blended refuges.